2018
DOI: 10.1007/s12519-017-0114-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine oral suspension in young pediatric patients with partial seizures and/or generalized tonic–clonic seizures in routine clinical practice in China: a prospective observational study

Abstract: This study, reporting the real-world data, further confirms the efficacy and good safety profile of OXC oral suspension in Chinese pediatric patients aged 2-5 years with PS and/or GTCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…We, therefore, set the highest dose of LEV as around 40 mg/Kg/d in this study aiming to avoid the potential side effects as far as possible. In line with a study that enrolled children aged 2–5 years ( 29 ), the most common AEs by OXC were rash (3.1%) and somnolence (2%). All AEs were of mild severity and were transient; the exception was one patient who withdrew from the OXC group due to medication-induced hypersensitivity syndrome.…”
Section: Discussionsupporting
confidence: 70%
“…We, therefore, set the highest dose of LEV as around 40 mg/Kg/d in this study aiming to avoid the potential side effects as far as possible. In line with a study that enrolled children aged 2–5 years ( 29 ), the most common AEs by OXC were rash (3.1%) and somnolence (2%). All AEs were of mild severity and were transient; the exception was one patient who withdrew from the OXC group due to medication-induced hypersensitivity syndrome.…”
Section: Discussionsupporting
confidence: 70%
“…Use of CBZ and OXC has previously been associated with relatively high rates of rash (3%‐19% and 3%‐8%, respectively). In addition, an analysis of AED‐induced SCARs found that CBZ was one of the major causative AEDs for this type of reaction .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] ESL is a dibenzazepine carboxamide derivative. Relatively high rates of rash have previously been observed with phenytoin and lamotrigine (LTG), and other dibenzazepine carboxamides such as carbamazepine (CBZ) and oxcarbazepine (OXC), 1,2,[12][13][14][15][16][17][18][19] and so it is relevant to examine to what extent allergic reactions also occur with ESL, and whether there may be any identifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of outcomes, there are favorable real-world evidence efficacy data in China for both CBZ and OXC in focal epilepsy [47][48][49]. In addition, OXC oral suspension is used in Chinese children for focal and generalized tonic-clonic seizures with substantial evidence for efficacy and safety [50,51] (Table 4). However, while OXC is approved in China for generalized onset tonic-clonic seizures in children it should be noted that it is not the case in some other countries including the US [50].…”
Section: Asiamentioning
confidence: 99%